Supraoptimal temperatures influence the range dynamics of a non‐native insect. Issue 7 (19th March 2014) - Tobin, Patrick C.; Gray, David R.; Liebhold, Andrew M.; Fitzpatrick, Matt
Abstract Aim To examine the relationship between the range dynamics of the non‐native species Lymantria dispar (L.) and supraoptimal temperatures during its larval and pupal period. Location West Virginia and Virginia, United States, North America. Methods We linked the annual frequency of supraoptimal temperatures during the larval and pupal period of L. dispar with annual changes in its range dynamics based upon a spatially robust 20‐year dataset. Correlation analyses were used to estimate the association between exposure time above the optimal temperature for L. dispar larval and pupal development, and the rate of invasion spread when adjusted for spatial autocorrelation. Results We documented L. dispar range expansion, stasis, and retraction across a fairly narrow latitudinal region. We also observed differences in the amount of exposure above the optimal temperature for L. dispar larval and pupal development across this region. Temperature regimes in the Coastal Plain and Piedmont regions of Virginia, where the L. dispar range has retracted or remained static, were warmer than those in the Appalachian Mountains of Virginia and West Virginia, where L. dispar has expanded its range. Our analyses at a smaller spatial scale confirmed a statistically negative association between exposure time above the optimal temperature for L. dispar larvae and pupae, and the rate of L. dispar invasion spread over the 20‐year period. Main conclusions The shifting, expansion and retraction of species distributional ranges holds critical implications to both invasion ecology and conservation biology. This work provides novel empirical evidence of the importance of supraoptimal temperatures on the range dynamics of a non‐native invasive insect with application to both non‐native and native species whose physiological processes are strongly regulated by temperature.